Landscape infrastructure developments and improvement in Malaysia: A review from 2000-2014 - Hj. Baharuddin, Zainul Mukrim (Science Publishing Corporation, 2019)
Since 20 years ago, Malaysian has recognized the landscape architectural industries and acknowledged its functions as importance as other professions in builds environments such as planners and architects. Malaysia aimed and committed to be a ‘tropical garden nation’ by 2020. The vision has inspired the landscape infrastructure developments and industries. The aim of the paper is to review landscape infrastructure development in Malaysia from 2000 to 2014. The study investigates the data using qualitative content analysis. It explores newspaper collection from the National Landscape Department website under the Housing and Local Government Ministry (KPKT) between year 2000 and 2014. The articles have been reviewed and folder under a code/theme that represents similar idea and content description. Thus, the study has found seven categories of issues. The higher percentage with 40% (108 articles) is Tree Planting Campaign, 16% (44 articles) is about Malaysia Landscape Identity, while Greening the Nation, Green Project and Development of Public Park score 14%. However, only fewer articles were found related to Housing Act and Management and Maintenance. The study concludes that the concept of ‘Garden Nation’ is the main trust in landscape infrastructure development in Malaysia. The concept will anchor and envelope all initiatives to inculcate the awareness of Malaysian to appreciate its beautiful green living environment including planning, design and implementation.